Analytical Review of Themes and Style in Christopher Marlowe’s Dr. Faustus - Ariremako Afolabi Innocent; Ebenezer Deji Ogunrinde; Oladele Jiboku (Britain International for Academic Research (BIAR-Publisher), 2025)
This study offers a critical examination of the central themes and stylistic techniques employed in Christopher Marlowe’s Doctor Faustus, with the aim of exploring how Marlowe integrates literary style and thematic concerns to construct a complex Renaissance tragedy. The theoretical framework adopted for this study is grounded in New Historicism and Formalist criticism, which allow for both contextual and textual analysis of the play. The study adopts a qualitative research design, relying on close textual analysis of selected scenes from the A-text version of Doctor Faustus. Key themes identified include the insatiable thirst for knowledge and power, the conflict between redemption and damnation, and the tension between free will and predestination. Prominent stylistic features examined include the use of soliloquy and allegory, which are shown to enrich character development and emphasise the play’s moral and philosophical dimensions. The findings reveal that Marlowe uses these themes and stylistic devices to dramatize the inner turmoil of the protagonist and to critique Renaissance ideals of intellectual ambition and human agency. The study concludes that Doctor Faustus remains a timeless and thought-provoking work, offering profound insights into the human condition through its interplay of style and theme.